BODY MASS INDEX AND PREDICTED PERCENT BODY FAT OF YOGYAKARTA AND FLORES PYGMY POPULATIONS - Hastuti, Janatin; T Rahmawati, Neni; A Suriyanto, Rusyad; Koeshardjono, Koeshardjono; T Jacob, T Jacob (Jurnal Kedokteran YARSI, 2008)
Body mass index and percent body fat are two parameters used to assess human body composition, which has several advantages for clinical practice, sport, growth, and normal population as well. There are many populations distributed in the wide Indonesian area that have various geographical characteristics. As evidence, plateau environments are inhabited by many populations whose physical and physiological traits are vary. This study was aimed to investigate body mass index (BMI) and predicted percent body fat (%BF) between Yogyakarta populations and Flores pygmy population in East Nusa Tenggara Province residing on a similar plateau environment. The present study was done on 105 people (51 males and 54 females) of Samigaluh Kulon Progo (Yogyakarta), 87 people (40 males and 47 females) of Gunung Kidul (Yogyakarta) and 75 pygmy people of Manggarai, Flores (East Nusa Tenggara). Height and weight were measured in all participants of this study. BMI was calculated from height and weight measurements and %BF was predicted based on BMI value using formula of Guricci et al (1998). Then, t-student test, linear regression, and chi square test were performed to analyze the data. The results indicated that Samigaluh and Gunung Kidul populations in Yogyakarta have considerably greater average of height and weight compare to Flores Pygmy population. However, differences in BMI and %BF were only significant between Flores Pygmy and Yogyakarta males population. Despite majority of both populations being under normal category, nutritional category based on BMI showed significant difference between Flores Pygmy and Yogyakarta population. In addition, more underweight individuals were also observed in Flores Pygmy. In conclusion, Yogyakarta population was considerably taller and heavier than Flores Pygmy population, however, in terms of %BF and BMI, they were nearly the same lean and body constitution. It is suggested that lower BMI and %BF represented by small body constitution and leanness in populations living on plateau in Yogyakarta and Flores are likely due to significant adaptation to their environment.